Memahami Spam Terhadap Digitalisasi Masyarakat Desa Perkebunan Sei Balai Kecamatan Sei Balai Kabupaten Batubara - Syafran Panggabean, Edwin; Chairul Indra Angkat; Dewi Sartika; Didi Riswan; Andysah Putera Utama; Muhammad Iqbal (Jurnal Pengabdian Masyarakat, 2023)
This community service aims to increase public understanding about spam messages regarding digitalization among the people of Batubara Regency, Sumatra Utara. This community service is carried out with a gradual socialization approach to the community of Perkebunan Sei Balai Village, Sei Balai District, Batubara Regency. The number of people involved in this community service program is 15 people, consisting of 7 men and 8 women, all of whom are housewives. The results of this community service found that the efforts made to increase public understanding of spam regarding digitalization have increased, this is proven by the results of discussions and good responses from the community in response to the community service program carried out. Apart from that, the community hopes that socialization will be carried out gradually and continuously to strengthen public understanding. This community service is quite effective and is recommended to be developed by combing through the most important areas considering that there is a phenomenon that the public's understanding of spam regarding digitalization is very low.